Assessment of Tocilizumab (Anti–Interleukin‐6 Receptor Monoclonal) as a Potential Treatment for Chronic Antibody‐Mediated Rejection and Transplant Glomerulopathy in HLA‐Sensitized Renal Allograft Recipients. Issue 9 (10th March 2017) - Choi, J.; Aubert, O.; Vo, A.; Loupy, A.; Haas, M.; Puliyanda, D.; Kim, I.; Louie, S.; Kang, A.; Peng, A.; Kahwaji, J.; Reinsmoen, N.; et al.
Abstract : Extending the functional integrity of renal allografts is the primary goal of transplant medicine. The development of donor‐specific antibodies (DSAs) posttransplantation leads to chronic active antibody‐mediated rejection (cAMR) and transplant glomerulopathy (TG), resulting in the majority of graft losses that occur in the United States. This reduces the quality and length of life for patients and increases cost. There are no approved treatments for cAMR. Evidence suggests the proinflammatory cytokine interleukin 6 (IL‐6) may play an important role in DSA generation and cAMR. We identified 36 renal transplant patients with cAMR plus DSAs and TG who failed standard of care treatment with IVIg plus rituximab with or without plasma exchange. Patients were offered rescue therapy with the anti–IL‐6 receptor monoclonal tocilizumab with monthly infusions and monitored for DSAs and long‐term outcomes. Tocilizumab‐treated patients demonstrated graft survival and patient survival rates of 80% and 91% at 6 years, respectively. Significant reductions in DSAs and stabilization of renal function were seen at 2 years. No significant adverse events or severe adverse events were seen. Tocilizumab provides good long‐term outcomes for patients with cAMR and TG, especially compared with historical published treatments. Inhibition of the IL‐6–IL‐6 receptor pathway may represent a novel approach to stabilize allograft function and extend patient lives. Abstract : Anti–interleukin‐6 receptor monoclonal tocilizumab preserves allograft survival and renal function with minimal side effects in >80% of patients with biopsy‐proven chronic antibody‐mediated rejection and transplant glomerulopathy who failed conventional treatment.